Hubungan faktor-faktor penyebab kecemasan dengan tingkat kecemasan suami menghadapi istri yang bersalin spontan - Emilda AS; Meliani Sukmadewi HRP (Poltekkes Kemenkes Yogyakarta, 2012)
Husband worried wife while accompanying the birth is influenced by several factors related to the level of anxiety. The aims of this study was to determine the relationship of these factors to the level of anxiety. Research using analytic study design with cross sectional method. Sampling using accidental sampling. Clinical research conducted in Medan Hadijah. Results of the study the majority of respondents aged 31-35 years by 25 people (48.1%), the majority of high school education 32 (61.5%), the majority of respondents earn Rp. 1000.000,00-Rp. 2000.000,00 as many as 29 people (55.8%). the wife of the safety factor and no influence fetal majority 40 (76.1%), the majority of factors influence gender expectations 27 people (51.9%), the factor of financial responsibility no influence 28 people (53.8%) and birth defects in children there are factors influence 31 people (59.6%). Data analysis used the chi square. Conclusion: no safety factor relationship with his wife and fetal levels of anxiety (p = 0.04), no correlation between gender expectations with the level of anxiety (p = 0.025), there was no correlation between the level of financial responsibility anxiety (p = 0.254), no correlation between children born with the defect levels of anxiety (p = 0.004). From the results of this research note that there are 3 factors associated with levels of anxiety husband.